Seismic risk assessment as part of the National Risk Assessment for the Republic of Cyprus: from probabilistic to scenario-based approach - Kazantzidou-Firtinidou, Danai; Kyriakides, Nicholas; Votsis, Renos; Chrysostomou, Christis (My University, 2022)
Seismic risk assessment for Cyprus at national scale is based on event-based probabilistic seismic risk analysis and eventual selection of seismic scenarios for given return periods. The current study was included in the National Risk Assessment of Cyprus, for 2018, following the European Commission requirements and guidelines. The latter analysis is performed with the relevant algorithm of Open Quake engine, which first incorporates stochastic event-based hazard analysis for extended earthquake catalogues and models of the area, as developed in the ESHM13 model developed in the SHARE project. The exposure model employed is built and elaborated by local resources, and the vulnerability model developed for local building typologies, as included in past publications, was used, with additional considerations. Risk is expressed in terms of monetary loss, at national level and for the biggest urban areas, and is provided in aggregated values as well as distributed along the island with map representation. For the selected scenarios, with 475- and 2500-year return period, expected casualties and displaced population are also estimated.
Keywords: Cyprus; Seismic risk; Disaster risk reduction; Probabilistic risk analysis; Seismic scenario